CULINARY HERITAGE AS AN OPPORTUNITY TO MAKE LUBELSKIE VOIVODESHIP’S TOURIST OFFER MORE ATTRACTIVE (E POLAND) - Skowronek, Ewa; Brzezińska-Wójcik, Teresa; Stasiak, Andrzej (Quaestiones Geographicae, 2019)
Lubelskie voivodeship has been standing out from other Polish administrative regions because of its agricultural function that has been shaped for centuries. Food and agricultural products originating in this region are seen as healthy, ecological and tradition-based. These resources have been noticed and used by the local government for building the regional brand and for promoting it. The main aim of this paper was to present the level of Polish people’s familiarity with lubelskie culinary heritage. Research findings obtained by means of the preliminary study and the diagnostic poll prove initiatives that have been undertaken to be effective. Inhabitants of other voivodeships do recognise lubelskie voivodeship and its culinary tradition, furthermore, a great majority know regional products from lubelskie. A development of tourism based on such a heritage is therefore an opportunity to make lubelskie voivodeship’s tourist offer more attractive. The offer may also become an important component for creating the brand.